The Pandemic’s Impact on Occupations, Livelihoods, and Well-Being - Lama, Ramesh Kumar; Malakar, Indra Mali (Historical Journal, 2025)
The COVID-19 pandemic, defined by WHO as the global spread of a noble disease, originating in Wuhan, China, in late 2019, disrupting economies and livelihoods worldwide. This paper examines the socioeconomic and health impacts of the pandemic in the Kathmandu District, focusing on three purposively selected municipalities: Kirtipur, Kathmandu Metropolitan, and Gokarneshwor. Adopting a pragmatic approach, the research combines both deductive and inductive reasoning. The majority of respondents were Hindu (79 percent), and 30.6 percent reporting a change in profession, primarily due to job losses and economic hardships caused by the pandemic. Most respondents (89.5 percent) resided in rented housing and 68.6 percent continued to pay rent despite financial difficulties. Food security emerged as a significant concern, with 87.7 percent of respondents emphasizing the need to save food for future use. Health issues were widespread, with 63.6 percent reporting health problems, including contracting COVID-19. Despite these challenges, 76.4 percent of those requiring treatment managed health expenses independently. Organizational support was limited, with only 37.3 percent receiving aid, predominantly in the form of food assistance from government bodies and NGOs. Preventive measures such as hygiene practices, masks wearing, and saving money were widely acknowledged. Significant associations were found between religion, marital status, and economic outcomes, highlighting their role in shaping respondents’ pandemic experiences. The findings emphasize the necessity for comprehensive support systems and targeted interventions during health crises.